2021
DOI: 10.1089/lgbt.2020.0490
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Gender Identity Change Efforts and Suicide Morbidity Among Sexual and Gender Minority Adults in Colombia

Abstract: Purpose: We assessed the association between sexual orientation and gender identity change efforts (SOGICE) experiences and lifetime suicide morbidity among sexual and gender minority (SGM) groups in Colombia. Methods: A sample of 4160 SGM Colombian adults responded to an online crosssectional survey. We used binary logistic regression to assess the relationship between SOGICE and suicide morbidity for the overall sample and stratified by SGM group. Results: We found a high prevalence of suicidal ideation (56%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Yet Blosnich et al (2021), for example, dismissed concerns that morbidity may have predated SOCE exposure in advocating a ban on SOCE due to its association with higher lifetime suicidal morbidity. Other recent studies have presented the same flawed form of argument (Ryan et al, 2020;Salway et al, 2020;del Río-González et al, 2021) that persons undergoing SOCE are more exposed, as a group, to minority stressors, which in turn induce greater personal harm. Blosnich et al (2020Blosnich et al ( , p. 1027Blosnich et al ( -1028, for example, attributed harm from SOCE to "the construct of perceived burdensomeness" resulting from minority stress, calling for further investigation into "specific constructs and mechanisms (e.g., enacted stigma, internalized stigma, and identity concealment) that could incite perceived burdensomeness and create the risk of suicidal thoughts and behaviors among survivors of SOCE."…”
Section: Discussionmentioning
confidence: 99%
“…Yet Blosnich et al (2021), for example, dismissed concerns that morbidity may have predated SOCE exposure in advocating a ban on SOCE due to its association with higher lifetime suicidal morbidity. Other recent studies have presented the same flawed form of argument (Ryan et al, 2020;Salway et al, 2020;del Río-González et al, 2021) that persons undergoing SOCE are more exposed, as a group, to minority stressors, which in turn induce greater personal harm. Blosnich et al (2020Blosnich et al ( , p. 1027Blosnich et al ( -1028, for example, attributed harm from SOCE to "the construct of perceived burdensomeness" resulting from minority stress, calling for further investigation into "specific constructs and mechanisms (e.g., enacted stigma, internalized stigma, and identity concealment) that could incite perceived burdensomeness and create the risk of suicidal thoughts and behaviors among survivors of SOCE."…”
Section: Discussionmentioning
confidence: 99%
“…We also found that lesbian and gay adults endorsed significantly greater odds of experiencing suicidal ideation almost every day during COVID-19 lockdown compared to heterosexual peers. Despite the dearth of literature examining sexual minority disparities in suicidality in Saudi Arabian and Indian samples, reports from other sexual minority samples suggest that sexual minority adults experience greater suicide risk due to multiple factors ( del Río-González et al, 2021 ; Nystedt et al, 2019 ; Suran, 2021 ). For sexual minority adults, syndemic factors such as stigmatizing and oppressive interpersonal and legislative acts, inadequate access to mental health services, and the politicization of public health may further exacerbate the existing disparities in suicidality risk ( Gibb et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gender identity change efforts (GICE), which seek to alter a transgender and/or nonbinary person's gender identity to be a cisgender identity, have been found to cause psychological and relational trauma (Del Río‐González et al, 2021; Goodyear et al, 2022; Green et al, 2020; Heiden‐Rootes et al, 2022; Turban et al, 2020). However, these practices continue to be used by therapists, and there are multiple states in the United States that do not have legal restrictions on the practice of GICE, leaving transgender and nonbinary people, especially transgender and nonbinary youth, at risk of being harmed (Green et al, 2020; Kinitz et al, 2022; Turban et al, 2019).…”
Section: Introductionmentioning
confidence: 99%